Random Decisions as Rational Decisions - Shao, Jianfei (Problemos, 2025)
Random decision-making (RDM) is a method of choice in which an agent delegates the final selection to a random device (e.g., a coin). When faced with multiple options, RDM is often dismissed as an irrational approach. Even in symmetrical cases where RDM is conceded to be rational, it is typically regarded as merely one among many equally effective methods for making an arbitrary choice. I challenge this prevailing view by pinpointing a unique psychological benefit of RDM – specifically, its capacity to mitigate potential regret – and thereby demonstrating that its rational applicability extends well beyond the narrow confines hitherto acknowledged. Once this capacity is recognized, it becomes clear that RDM is the uniquely rational strategy in certain symmetrical dilemmas while remaining rational in some asymmetrical cases. Furthermore, while factors such as affective and sociocultural influences impose limitations on the practice of RDM, I contend that these constraints are not insurmountable and may be mitigated as a deeper understanding of RDM’s unique value emerges.